2021
DOI: 10.1039/d1ma00467k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized graphene oxide materials for the fluorometric sensing of various analytes: a mini review

Abstract: In this review, we critically discuss the sensitive and selective recognition of biologically and environmentally important varied analytes based on the functionalized graphene oxide (GO) materials due to their ubiquitous advantage among the diverse nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…GO is a chemically exfoliated graphene derivative, which can be utilized as a fluorescence quencher for various fluorescent probes, such as fluorescent polymer [76,151,152], fluorescent protein [68], metal nanodots [153], and fluorescently labeled DNA [69,[154][155][156][157][158]. More importantly, GO showed differential affinity toward different molecules or materials [159,160].…”
Section: Graphene Oxide (Go)-based Sensor Arraysmentioning
confidence: 99%
“…GO is a chemically exfoliated graphene derivative, which can be utilized as a fluorescence quencher for various fluorescent probes, such as fluorescent polymer [76,151,152], fluorescent protein [68], metal nanodots [153], and fluorescently labeled DNA [69,[154][155][156][157][158]. More importantly, GO showed differential affinity toward different molecules or materials [159,160].…”
Section: Graphene Oxide (Go)-based Sensor Arraysmentioning
confidence: 99%
“…Over the years, graphene-based nanomaterials have been utilized for various applications, such as in energy, photoelectronic, catalyst, biomedicine, and sensing fields [22][23][24][25]. To date, various review articles in the field of sensing utilizing graphene-based materials have been reported [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions involving π-systems are most relevant in the context of the design and fabrication of nanodevices based on graphene, as they can induce dramatic effects in the structure and properties of the system, including dispersibility, mechanical strength, stability, flexibility, electrocatalytic properties, and so on, ensuring extended applications. 4–8…”
Section: Introductionmentioning
confidence: 99%